Peran Serta Masyarakat Dalam Pengelolaan Taman Nasional Gunung Merbabu di Desa Jeruk Kecamatan Selo, Kabupaten Boyolali - Sadono, Yulian (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2013)
Taman Nasional Gunung Merbabu (Mt. Merbabu National Park) located in Boyolali is a conservation area serving ecologic and economic functions to communities in the surrounding. The study examines the form and level of participation of the local community in Jeruk Village, one of the national park’s buffer area, along with the factors affecting them. Analysis showed that the community in Jeruk Village tend to be homogenous, with most of the pople having low level of income an education, therefore their contribution can only be practiced in the form of ideas, suggestions and sheer power. At the planning stages, the community’s role is consultative; the national park’s management tend to be dominating the program planning and design, while the community simply goes along with the activity by getting incentives. In monitoring and protecting the area, the community in Jeruk Village established a voluntary security force, with autonomous financing. The main factor driving the community to participate is to protect the national park’s ecological function as to preserve the water cycle and prevent floods. The study has found a need for an institutional strengthening so that the community may have a stronger bargaining position in practicing its participation.